Intracellular TLR22 acts as an inflammation equalizer via suppression of NF-κB and selective activation of MAPK pathway in fish. Issue 72 (January 2018) - Ding, Xu; Liang, Yaosi; Peng, Wan; Li, Ruozhu; Lin, Haoran; Zhang, Yong; Lu, Danqi
Abstract: TLR22, a typical member of the fish-specific TLRs, is a crucial sensor in virally triggered innate immune signalling retained from natural selection. To elucidate the role of the TLR22-specific signalling cascade mechanism, we provide evidence that the double-stranded (ds) RNA-sensor TLR22 positively regulates the ERK pathway and negatively regulates the JNK, p38 MAP kinase and NF-κB pathway. Here, we show that TLR22 restrains NF-κB activation and IFN (interferon) β and AP-1 (activator protein-1) promoter binding (impairing "primary response" genes (TNF and IL-1)), induces "secondary response" genes (IL-12 and IL-6) and mediates the irregular expression of inflammatory genes. Therefore, TLR22 promotes ERK phosphorylation but impairs the JNK and p38 MAP kinases and IκB phosphorylation. Additionally, TLR22 controls the excessive generation of reactive oxygen species (ROS) to avoid damaging the organism. The specific kinetics of TLR22 depends on its distinct cellular localization. We demonstrate that TLR22 is an intracellular receptor localized in the endosome, and the TLR22-TIR domain is the functional structure inducing the signalling cascade post-viral replication in the body. As mentioned above, our data reveal a novel mechanism whereby TLR22-induced positive adjustment and negative regulation evolved independently to avoid harmful and inappropriate inflammatory responses. Highlights: The first study to demonstrate TLR22 is an intracellular receptor localized in the endosome. The TIR domain of intracellular TLR22 is the functional structure inducing a novel mechanism. TLR22 positively regulates the ERK pathway and negative regulates the JNK, p38 MAP kinase and NF-κB pathway.